2020
DOI: 10.1109/access.2020.2994620
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Anti-Interference Low-Ambiguity Dual-Frequency Multiplexing Modulation Based on the Frequency-Hopping Technique

Abstract: To improve the anti-interference performance and mitigate the autocorrelation function (ACF) ambiguity of dual-frequency multiplexing modulation, we propose a new type of modulation: frequencyhopping alternated binary offset carrier (FH-AltBOC) modulation based on the frequency-hopping technique. The new modulation is generalized and includes AltBOC modulation, so it inherits the advantages of AltBOC modulation while also exhibiting new properties, such as low ambiguity, low probability of intercept, and bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Medium access control level [142][143][144][145][146] The FH technique is employed for mitigating the effects of the IPCs. The information obtained in all the available channels is used for increasing the ranging accuracy, which will result in the improvement of the localization accuracy.…”
Section: Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium access control level [142][143][144][145][146] The FH technique is employed for mitigating the effects of the IPCs. The information obtained in all the available channels is used for increasing the ranging accuracy, which will result in the improvement of the localization accuracy.…”
Section: Mitigationmentioning
confidence: 99%
“…Recently, a fast frequency hopping (FH) technique has been employed not only for mitigating the effects of MPCs but also for reducing signal interference [142,144]. It has also been shown that, by increasing the number of subcarriers, the mitigation of the IPCs can be enhanced [146]. Although FH techniques are useful for mitigating the effects of MPCs, there are open issues that need to be carefully addressed such as hop impairments (e.g., phased offset and group delay), especially for time-based localization techniques [145,167].…”
Section: ) Mitigation Of Multipath Componentsmentioning
confidence: 99%
“…Therefore, to avoid high-precision calibration and the increase in system complexity, multiple elements adopting the same hardware receiving channel can effectively solve the measurement accuracy problem caused by channel inconsistency. 6,7 In this article, an interferometer DF system based on spread spectrum signals is presented. The antenna receiving channel is simplified by multichannel time-division multiplexing.…”
Section: Introductionmentioning
confidence: 99%
“…The phase inconsistency of uncalibrated channels will lead to a decrease in measurement accuracy and even incorrect DF results. Therefore, to avoid high‐precision calibration and the increase in system complexity, multiple elements adopting the same hardware receiving channel can effectively solve the measurement accuracy problem caused by channel inconsistency 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Frequency-hopping (FH) signals are generated by varying the carrier frequency according to a pseudo-random pattern. Owing to their inherent advantages, namely a low probability of being intercepted, flexible networking capabilities, resistance to jamming and multipath fading, FH signals have become an appropriate choice and are widely used in satellite communications [1], wireless communications [2,3], physical layer security [4,5], smart grids [6,7], underwater communication [8,9], Internet of Things (IoT) technology [10,11], and unmanned aerial vehicles (UAV) [12,13]. In the fields of interference analysis and communication security, estimating the parameters of FH signals and tracking them is a highly challenging, but crucial, task when the hopping patterns are unknown.…”
Section: Introductionmentioning
confidence: 99%